2017
DOI: 10.1093/jee/tow260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carriers, Emulsifiers, and Biopesticides for Direct Silk Treatments on Caterpillar Feeding Damage and Ear Development in Sweet Corn

Abstract: In the northeastern United States, control of Lepidopteran pests of sweet corn, particularly corn earworm [Helicoverpa zea (Boddie)], is difficult using organic methods. The direct application of corn oil and Bacillus thuringiensis (Bt) to corn silk has been shown to reduce ear damage from corn earworm in past studies; these studies sought to optimize this method by evaluating additional carrier and biopesticide mixtures that comply with the United States Federal Insecticide, Fungicide, and Rodenticide Act and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Alternative insecticides are relatively common in scientific literature. Westgate et al [124] reported on several methods of control of Lepidopteran pests of sweet corn, particularly corn earworm, using organic methods. Direct application of corn oil and B. thuringiensis to corn silks reduces ear damage.…”
Section: Insecticidesmentioning
confidence: 99%
“…Alternative insecticides are relatively common in scientific literature. Westgate et al [124] reported on several methods of control of Lepidopteran pests of sweet corn, particularly corn earworm, using organic methods. Direct application of corn oil and B. thuringiensis to corn silks reduces ear damage.…”
Section: Insecticidesmentioning
confidence: 99%